(untitled) (Research, Society and Development, 2020)
Technologies are present in everyday school life through different means. So, why not use them in favor of teaching? Thus, the present research aimed to investigate contributions of educational technologies, as well as to test how the digital game developed in the scope of this research provides teaching-learning processes. The research has an exploratory, qualitative, quantitative and investigative character, with collected data being predominantly descriptive. The research sample is non-probabilistic and the procedure for analyzing the questionnaires occurred through the Content Analysis proposed by Bardin (2016). As data collection instruments, semi-open questionnaires applied to teachers in training. The results showed that, for the most part, technologies can help and contribute to the teaching-learning process and still believe that the non-use of these technologies may be linked to the lack of equipment or to the aversion to new methodologies. Regarding the digital game, most respondents believe that it positively influenced the learning of scientific concepts and that it would be feasible to take the technologies to the classroom context in order to make them more motivating. It was found that the game developed contributed to the learning of biology concepts, including it in the context of innovative methodologies for teaching practice.